2014
DOI: 10.1177/1359104514538040
|View full text |Cite
|
Sign up to set email alerts
|

Understanding conduct disorder: The ways in which mothers attempt to make sense of their children’s behaviour

Abstract: 'Disruptive behaviour disorders' are the most common reason for referral to Child and Adolescent Mental Health Services (CAMHS). Current treatment guidelines focus on parent-training programmes. Difficulties are often reported when engaging families, with parental attributions and attitudes towards help-seeking proposed as influential factors. Previous research has tended to privilege pre-existing frameworks; this study utilised qualitative methods to add to the current understanding of the ways in which paren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Qualitative research on parenting children with CP is surprisingly rare, thus lending little insight into the nature of the struggles that parents of children with CP face on a daily basis. In a recent study by Lewis et al [ 22 ] examining how parents ‘made sense’ of their child with CP, parents describe difficulties in dealing with their child’s emotional behaviour, as well as the impact that the child’s behaviour had on their own emotions. Webster-Stratton et al [ 40 ] qualitatively explored the effects that the CP child had on the family unit and found challenges with siblings and family and marital discord, as well as challenges faced by the family in the community.…”
Section: Introductionmentioning
confidence: 99%
“…Qualitative research on parenting children with CP is surprisingly rare, thus lending little insight into the nature of the struggles that parents of children with CP face on a daily basis. In a recent study by Lewis et al [ 22 ] examining how parents ‘made sense’ of their child with CP, parents describe difficulties in dealing with their child’s emotional behaviour, as well as the impact that the child’s behaviour had on their own emotions. Webster-Stratton et al [ 40 ] qualitatively explored the effects that the CP child had on the family unit and found challenges with siblings and family and marital discord, as well as challenges faced by the family in the community.…”
Section: Introductionmentioning
confidence: 99%
“…It can be assumed that the complexity emerging from the findings as to the experience of ultra-orthodox parents who send their child for arts therapies is related to the characteristics of the ultra-Orthodox community, which is described in the literature as a collective culture in which the community plays a central role in the individual’s life [ 12 ]. The social context apparently added further complexity to the parents’ already complex experience, since significant difficulties in a child may overwhelm parents with difficult emotions such as anger, frustration, shame and guilt, such that parents may perceive seeking out therapy as an indication that they are ‘bad parents’ or unable to cope [ 39 ]. Nonetheless, some other parents who participated in the current study resisted this stigma and expressed acceptance of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the participating parents took a purpose-oriented attitude towards therapy. This attitude is also found in the general population, and it is expressed, for example, in wanting therapy to provide a quick-fix solution to their children’s problem once and for all [ 39 ]. However, in the present case this purpose-oriented position tended to dominate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is consistent with those of Maniadaki and colleagues [ 83 ], which indicated that mothers tended to rate conduct problems as being more severe and more negatively impacting their children’s lives than ADHD behaviors. One possible explanation raised by Lewis and colleagues [ 84 ] is that mothers of children with oppositional behaviors have difficulty integrating the conflicting views of their child’s behavior, which is associated with strong emotional reactions. Indeed, they could describe them as “manipulative” on the one hand and “vulnerable” on the other.…”
Section: Discussionmentioning
confidence: 99%